A Palladium Catalyst Supported on Boron-Doped Porous Carbon for Efficient Dehydrogenation of Formic Acid - Hui Liu; Mengyuan Huang; Wenling Tao; Liangliang Han; Jinqiang Zhang; Qingshan Zhao (Nanomaterials, 2024)
Formic acid has emerged as a highly promising hydrogen storage material, and the development of efficient catalysts to facilitate its dehydrogenation remains imperative. In this study, a novel catalyst consisting of palladium nanoparticles supported on boron-doped porous carbon (Pd/BPC) was successfully synthesized to enable efficient hydrogen production through the dehydrogenation of formic acid. The impacts of the boron doping ratio, doping temperature, and palladium reduction temperature on the catalyst’s performance were systemically investigated. The results demonstrated the Pd/BPC catalyst synthesized with a carbon-to-boron ratio of 1:5 by calcination at 900 °C and subsequent reduction at 60 °C exhibited superior formic acid dehydrogenation performance, being 2.9 and 3.8 times greater than that of the Pd/PC catalysts without boron doping and commercial Pd/C, respectively. Additionally, the catalyst showed excellent cycle stability with no significant activity reduction after five consecutive cycles. Experimental and theoretical results reveal that boron doping not only facilitates the homogenous distribution of Pd nanoparticles but also induces a stronger support–metal interaction, thereby reinforcing the catalytic performance. This research is expected to provide valuable insights into the economically viable and efficient production of environmentally friendly hydrogen energy.